HIIT & RT or RT & HIIT: The order of stimulations alters acute hemodynamic response? - Oliveira-Silva, Iransé; Silva, Samuel Gomes; Santana, Fábio (Manual Therapy, Posturology & Rehabilitation Journal, 2021)
Background: The High Intensity Interval Training (HIIT) has had space in social networks that disseminate its practice and also among practitioners of physical exercises in a global way. Objective: To verify if the stimuli order (HIIT-RT or RT-HIIT) changes the acute hemodynamic response. Methods: 10 young adult male participants aged between 18 and 30 years (24.7 ± 2.2). For the test protocols the High intensity interval training (HIIT) and the conventional resistance training (RT) were performed in Cross-over using a Spinning Exercise Bike in addition to the apparatus: Bench press; Leg Press; Pull down; Leg curl; Low Rower. The hemodynamic variables were collected at rest, post-training, and 10 ’, 20’ and 30 ’minutes of recovery. Results: A significant difference was found in HR and SBP at the end of the training in the SBP and DBP variables there were significant differences in the 20’ and 30’ minutes and in the MAP there was a significant difference in all recovery times with RT and HIIT higher post-workout and recovery values. Conclusion: the stimuli order changes the acute hemodynamic response. When the orders were analyzed (HIIT-RT; RT-HIIT), the order that presented the best results was HIIT-RT. It presented changes during exercise as they presented better post-training responses.